2020
DOI: 10.1016/j.jmb.2020.02.016
|View full text |Cite
|
Sign up to set email alerts
|

The Basal Level of Gene Expression Associated with Chromatin Loosening Shapes Waddington Landscapes and Controls Cell Differentiation

Abstract: The baseline level of transcription, which is variable and difficult to quantify, seriously complicates the normalization of comparative transcriptomic data, but its biological importance remains unappreciated. We show that this currently neglected ingredient is essential for controlling gene network multistability and therefore cellular differentiation. Basal expression is correlated to the degree of chromatin loosening measured by DNA accessibility, and systematically leads to cellular dedifferentiation as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…Whilst a CSC model in which these cells unidirectionally give rise to both CSCs and non-CSCs holds true in some neoplasias, it appears that non-CSCs can also revert to a CSC state. Indeed, the dynamic gene regulatory networks underpinning both CSCs and non-CSCs states are sustained by feedback loops, whose epigenetic dysregulation can lead to cell state conversion [28][29][30][31][32]. Additional studies have suggested that CSCs may be metastatic and resistant to therapy, which poses major therapeutic challenges [30,33].…”
Section: Plasticity and Stemnessmentioning
confidence: 99%
“…Whilst a CSC model in which these cells unidirectionally give rise to both CSCs and non-CSCs holds true in some neoplasias, it appears that non-CSCs can also revert to a CSC state. Indeed, the dynamic gene regulatory networks underpinning both CSCs and non-CSCs states are sustained by feedback loops, whose epigenetic dysregulation can lead to cell state conversion [28][29][30][31][32]. Additional studies have suggested that CSCs may be metastatic and resistant to therapy, which poses major therapeutic challenges [30,33].…”
Section: Plasticity and Stemnessmentioning
confidence: 99%
“…Theoretically, cell-fate transitions and switch-like behavior has been modeled in terms of gene-regulatory networks (GRNs) and an associated system of ordinary differential equations (ODEs) that describe the dynamic changes in TF concentrations. 4 , 7 , 8 , 9 In most cases however, the full underlying GRNs are unknown, and the associated ODEs typically include many unknown parameters whose precise values may strongly affect the resulting dynamics, rendering this ODE-modeling approach impractical. In the face of these difficulties, single-cell RNA-Seq (scRNA-Seq) data 10 and other single-cell omic data types 11 offer the unprecedented opportunity to study the underlying bifurcation dynamics from a more data-driven perspective, as exemplified by the development of numerous lineage-trajectory inference algorithms 12 , 13 and statistical methods to detect TFs controlling the cell-fate commitment process.…”
Section: Introductionmentioning
confidence: 99%